Insistence of Some Muslim Religious Scholars in Kogi State Nigeria on Pre-Marital Pregnancy Test Before Marriage - Ummulkhayr Adamu; Atiku Garba Yahaya (Bulletin of Islamic Research, 2026)
Purpose: This study examines the growing insistence by some Muslim religious scholars in Kogi State on requiring pre-marital pregnancy tests for prospective brides before solemnizing Islamic marriage contracts. It aims to evaluate the religious legitimacy, ethical implications, and social consequences of this practice within the broader framework of Islamic teachings on marriage, dignity, and the protection of lineage (ḥifẓ al-nasl). Design/methods/approach: The research employs a qualitative and analytical methodology. Primary sources include the Qur’an, Hadith literature, and classical works of Islamic jurisprudence. Secondary sources consist of scholarly books, peer-reviewed journal articles, and contemporary reports concerning Muslim social practices in Nigeria. Data were analyzed through normative Islamic legal reasoning and contextual socio-religious interpretation. Findings: The study finds that supporters of pre-marital pregnancy testing argue that the practice helps prevent disputes over paternity, safeguards family honour, and discourages immoral conduct. Conversely, critics maintain that compulsory testing may violate personal dignity, foster suspicion between families, and lacks an explicit textual basis in Islamic law. The findings further indicate that while Islam strongly emphasizes moral conduct and lineage preservation, coercive implementation of such tests may conflict with Islamic values of justice, privacy, and human dignity. Research implications/limitations: This study is limited to a conceptual and textual analysis centered on the socio-religious context of Kogi State and does not include extensive field interviews or quantitative community data. Future studies may incorporate empirical perspectives from scholars, families, and marriage registrants across different Muslim communities. The research contributes to contemporary discussions on balancing Islamic legal objectives with evolving social realities. Originality/value: This paper offers an original contribution by critically exploring the emerging practice of pre-marital pregnancy testing in a Muslim African context through the lens of Islamic jurisprudence and ethics. It provides a nuanced framework for understanding how religious authority, communal morality, and individual rights interact in contemporary Muslim marriage practices